Exploring physicochemical property and food safety in dried shrimp production: Risks and mitigation strategies - Fauziah Fitriana; Saran Anuntawirun; Nawaphorn Roongrojmongkhon; Piyachat Dachsri; Edward R. Atwill; Anyarat Thiptara; Saharuetai Jeamsripong (PLoS ONE, 2026)
Dried shrimp is a widely consumed aquatic product whose safety and quality depend on various physicochemical and microbiological properties influenced by production practices. This study aimed to assess the physicochemical characteristics and levels of bacterial contamination occurring in small-scale dried shrimp production and to propose practical mitigation strategies. Samples of dried shrimp were collected from Nakhon Si Thammarat and Surat Thani, Thailand and analyzed for moisture content, water activity, pH, salt concentration, and bacterial contamination; in addition, we collected information regarding each farmer’s production practices. The main shrimp species were Parapenaeus longipes and Acetes spp. Only 52.0% of samples met the moisture content standard. Production practices, particularly post-cooking handling, were identified as critical points for re-contamination and/or regrowth. While cooking reduced bacterial loads, subsequent handling stages led to significant increases in bacterial loads, emphasizing the need for improved hygiene during post-cooking handling. Average reported measurements from all shrimp species were salt (7.8 ± 5.3 g/100g), moisture (31.2 ± 11.1 g/100g), water activity (0.8 ± 0.09), and pH (7.9 ± 0.33). High overall prevalence of total coliforms (94.0%), fecal coliforms (41.3%), and Escherichia coli (26.4%) were found, with exceedances of standard limits at 71.6%, 19.4%, and 26.4%, respectively. Salmonella enterica subsp. enterica (1.0%; n = 2/201), Staphylococcus aureus (2.5%; n = 5/201), and Vibrio cholerae (2.0%; n = 4/201) were identified at low frequencies. The serovars of Salmonella were Tallahassee and Mount Pleasant. The mean microbial load of S. aureus samples was 4.2 logCFU/g, and all these samples exceeded the microbiological limit of 100 CFU/g set by the Thai Agricultural Standard. Negative binomial regression identified pH, sampling location, shrimp color, and fecal coliforms as predictors of E. coli levels. This study highlights the importance of microbial safety and quality assessment in dried shrimp production, emphasizing the need for stringent hygiene controls and critical control point management to prevent post-processing contamination and to ensure high product quality.